Comparison Between Forehand and Backhand Stroke Techniques in the Accuracy of Strikes Among Extra-Curricular Table Tennis Students at State Senior High School 1 Sedayu - Hidayat, Wahyu; Falaahudin, Ardhika (Pusdikra-Publishing.com, 2024)
This research is a descriptive study. The method used is a survey. The study population consists of 12 students participating in table tennis extracurricular activities at SMA Negeri 1 Sedayu. Data collection techniques employed in this research include testing and measurement. The results of the study indicate that (1) Forehand stroke abilities in table tennis extracurricular activities at SMA Negeri 1 Sedayu fall into the